2020
DOI: 10.1177/2150132720969557
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Primary Care Visits in the 24 Weeks After COVID-19 Stay-at-Home Orders Relative to the Comparable Time Period in 2019 in Metropolitan Chicago and Northern Illinois

Abstract: Objective In this brief report, we characterize pediatric primary care service utilization in metropolitan Chicago over the first 24 weeks of the COVID-19 pandemic response in relation to the comparable time period in 2019. Methods We examined retrospective visit and billing data, regardless of payer, from 16 independent pediatric practices that utilize a common electronic medical record platform within an Accountable Care Organization of 252 pediatricians in 71 offices throughout metropolitan Chicago. We cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…[ 8 , 9 , 10 , 11 ]. However, our study adds to the sparse literature, by evaluating 79 clinics across four large, academic institutions in the Southeastern US, indicating decreased utilization of pediatric primary care [ 12 , 19 ]. Reasons for decreased primary care visits include patients’ fear of contracting the SARS-CoV-2 infection [ 11 , 18 ], practices deferring elective visits [ 21 ], governmental stay at home orders [ 9 ], and decreased infection-related visits [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 8 , 9 , 10 , 11 ]. However, our study adds to the sparse literature, by evaluating 79 clinics across four large, academic institutions in the Southeastern US, indicating decreased utilization of pediatric primary care [ 12 , 19 ]. Reasons for decreased primary care visits include patients’ fear of contracting the SARS-CoV-2 infection [ 11 , 18 ], practices deferring elective visits [ 21 ], governmental stay at home orders [ 9 ], and decreased infection-related visits [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 9 , 10 , 11 ]. There has also been a decrease in pediatric primary care visits due to concerns about children becoming infected with SARS-CoV-2, or in order to comply with stay-at-home orders [ 12 ]. During March and April 2020, restaurants, bars, public schools, and nonessential businesses were closed for in-person services and large gatherings were prohibited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In March, the Governor of Illinois issued a stay‐at‐home executive order limiting health care seeking to emergencies and COVID‐19 care, closing schools to in‐person instruction, and restricting daycare to groups of 10 or fewer children of essential workers. The stay‐at‐home order was associated with substantial reductions in health care utilization by children in metropolitan Chicago and northern Illinois; well‐child examinations recovered to prepandemic levels by June while other visit types remained suppressed through summer 2020 5 …”
Section: N Proportion Of Caregivers Hesitant To Seek Emergency Care mentioning
confidence: 99%
“…During the first wave of COVID‐19 in metropolitan Chicago, we found that nearly one in four caregivers were hesitant to seek ED care for their child with a hypothetical emergency condition. Prior to declines in acute health care utilization associated with the COVID‐19 pandemic, 3‐5 higher ED utilization has been observed among children who are African American/Black or Latinx and publicly insured 7 . Researchers focused attention on low‐acuity ED visits for children 7,8 …”
Section: N Proportion Of Caregivers Hesitant To Seek Emergency Care mentioning
confidence: 99%